Changes in Antibiotic Susceptibility of Helicobacter pylori in the Course of Eight Years in the Zaanstreek Region in The Netherlands - R. J. L. F. Loffeld; B. F. M. Werdmuller (Gastroenterology Research and Practice)
Background. Failure of anti-Helicobacter therapy is the result noncompliance and resistance to the prescribed antibiotics. Aim. Antibiotic susceptibility of H. pylori was determined in native Dutch patients and patients of Turkish descent. Methods. In a period of eight years a total of 925 strains of H. pylori were cultured. Bacterial susceptibility was successfully determined in 746 (80.6%) of these isolates. Three hundred and nine strains (33%) originated from patients of Turkish descent. Results. In total clarithromycin resistance was found in 146 (20.5%) strains, metronidazole resistance in 147 (19.9%) strains. Amoxicillin resistance was found to be present in five strains. There is a slight but nonsignificant decrease in the percentage of clarithromycin-resistant strains in the consecutive period of eight years from 20% to 18%. No changes were seen in the consecutive years in metronidazole resistance. The number of clarithromycin-resistant strains decreased in Turkish patients, not in native Dutch patients. Conclusion. Resistance did not change significantly in consecutive years. But clinicians should take not only the antibiotic history into account but also ethnicity before prescribing metronidazole or clarithromycin.